AKTIVITAS HARIAN MERAK HIJAU (Pavo muticus) DI DALAM KANDANG DI KAMPUS IPB DRAMAGA: Daily Activities of Green Peafowls (Pavo muticus) in Cage at IPB Dramaga Campus - Syahras Fathin Aminuddin; Ahsani Taqwim; Fauzia Noorchaliza; Tri Heru Widarto (Jurnal Sumberdaya Hayati, 2026)
The study aimed to examine differences in the daily activities of Green peafowl (Pavo muticus) by gender at IPB Dramaga, Bogor. The observation was conducted on two individuals of Green peafowl (one adult male and one adult female) using the focal animal sampling method, with each observation duration of 30 minutes. Daily behavioral data were grouped into 13 observation time ranges. Differene in behavior across observation times were analyzed using the Friedman, while differences between male and female weretested using the Mann-Whitney U test.The results of the analysis show that the highest use of time in the daily behavior of green peafowl is investigative behavior and self-care (>30%), and based on observation time, investigative behavior shows significantly different (p<0.05), while other behaviors are not significantly different (p>0.05). Furthermore, pecking and resting behavior in females was significantly (p<0.05) higher than in males, while display behavior in males was significantly (P<0.05) higher than in females. The conclusion of this study, based on the observation time, is that there are differences in variations in daily behavior of birds (investigative behavior) and in daily behavior (pecking, resting and displaying) based on gender. It is necessary to separate cages by gender outside the mating season and to add feeding areas to ensure animal welfare.